Making IT work : a history of the computer services industry - Yost, Jeffrey R. 1967- (History of computing, 2017)
Introduction -- Industry origins -- Constructing expertise : Arthur Andersen, Diebold, and Canning-Sisson, 1953-1964 -- Processing data : IBM-SBC and automatic data processing, 1953-1964 -- Programming machines : computer usage, C-E-I-R, and computer sciences, 1955-1967 -- Integrating systems : system development and informatics, 1955-1969 -- Industry identity -- Cooperating competitors : ADAPSO, 1961-1982 -- Managing facilities : electronic data systems, 1962-1984 -- Sharing time : tymshare, 1965-1984 -- Expanding capabilities : IBM and Control Data, 1960-1988 -- Brokering contractors : Gentry Inc., Phyllis Murphy, COMSYS, and the NACCB, 1972-1998 -- Geographical and organizational change -- Transforming giants, offshoring work, and creating clouds : IIBM, HP, Accenture, Fujitsu, Capgemini, India's Big Five, Microsoft, Google, Amazon, and Saleforce.com, 1982-2016 -- Conclusion -- Notes -- Index